TARGETED ACTIVITIES IN GROUP CONTEXTS The analysis of activities to meet consumer need - Phillips, Julie (Groupwork, 2020)
This article acknowledges the lack of analytical frameworks to aid the practitioner in selecting and organising activities to meet the needs of individuals and groups in residential, day care, and a wide range of social groupwork settings. The contribution of the relevant literature is reviewed. The results of the author’s use of a framework to analyse activities in a day centre for people recovering from mental illness are described. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are to some extent searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.